Los efectos perturbadores en las relaciones entre variables (ING) - Chaves Esquivel, Edwin (2002)
This article evaluated the importance of analyzing the disturbing effect that a specific characteristic can cause between two or more variables. In order to analyze the problem, it was used information got from a questionnaire that was applied to a sample of primary teachers on 1998. Through concrete examples it is possible to observe how the apparent statistical dependence between two variables disappear when its effect is controlled using a third characteristic. This happens because the variables used to explain a specific phenomenon are strongly correlate among them. This correlation sometimes causes a false effect on the original relation. The analyses are made by contingency tables and Chi-Square test. These tools showed their utility to determine some of the confused effects among the variables.